Iconicidade lexical na constituição de uma narrativa de extração histórica : uma análise do romance “A casca da serpente” - (:unkn) unknown (Universidade Estadual de Goiás, 2024)
The Theory of Verbal Iconicity, developed by the renowned Brazilian linguist/semioticist Darcilia Simões, points out that verbal texts are constituted from verbal iconicity triggered by the lexical c hoices made by the author. Supported by this theory, this research aims to understand how the novel A Casca da Serpente, by José J. Veiga, constitutes a narrative of historical extraction based on its lexical index. To achieve this goal, the theoretical me thodological contribution of the Verbal Iconicity Theory (Simões, 2009, 2019) and narrative theory was adopted. reflections on narratives of historical extraction (Trouche, 2006) and the methodological basis of Corpus Linguistics (Assis, 2018; Sardinha, 2 004, 2009). The results of this study, in this sense, reveal that the plot, characters, time, space and narrator of the novel corpus are indispensable elements in the constitution of the extraction material as they are iconically constituted by the choices made by the author. Furthermore, the research proves that the use of the WordSmith Tools program, a Corpus Linguistics tool, makes it possible to survey/map the lexical items that corroborate the organization of the Veiguian historical extraction narrativ e. Given these results, it is concluded that the textual plot of A Casca da Serpente is constructed by the lexical index in order to retell the official history of the Guerra de Canudos and of Antônio Conselheiro, presenting certain distortions (exaggerati ons, additions, omissions), an indispensable trait of a literary narrative.
Keywords: Iconicidade lexical; Romance de extração histórica; A casca da serpente; Lexical iconicity; Romance of historical extraction; LINGUISTICA, LETRAS E ARTES; LETRAS::LINGUA PORTUGUESA